Introduction to programming using Java : an object oriented approach - Arnow, David M. (Pearson, 2004)
"This introductory programming book, thoroughly updated for the Java 2 release, offers a truly object-oriented focus. The concepts of object, class, and message are presented as early as Chapter 1. This object-oriented approach is then used throughout as students learn the fundamentals of object-oriented programming along with the basics of imperative programming. The authors place a strong emphasis on the software development process, presenting a clear and usable problem-solving procedure for developing classes that is used throughout the book."--BOOK JACKET.